THE EFFECT OF TRANSLATION ON SECOND LANGUAGE LEARNING - Ozoda Rustamova; Eshmamatova Mukhlisa (JOURNAL OF NEW CENTURY INNOVATIONS, 2025)
Abstract. Translation has long been a debated method in second language (L2) education. This study examines its impact on vocabulary retention, grammatical understanding, and cultural competence among adolescent learners aged 15–18. Utilizing a mixed-methods approach with 120 intermediate-level students, data were collected through translation tasks, proficiency tests, and learner feedback. Findings indicate that translation enhances vocabulary retention and cultural understanding, while also aiding grammatical comprehension. However, challenges such as over-reliance on the first language (L1) and literal translations present limitations. The study suggests that strategic integration of translation into modern teaching methods can contribute to a balanced and effective learning process for adolescents.